A correlation between two pairs of linear relations and dissipative extensions of some nondensely defined symmetric operators. - Storozh, O.G. (Carpathian Mathematical Publications, 2009)
A general form of a maximal dissipative subspace extension (in particularly of an operator extension) of a finite-dimensional nondensely defined restriction of a symmetric operator with arbitrary defect numbers is established.